2021
DOI: 10.4103/0973-029x.325232
|View full text |Cite
|
Sign up to set email alerts
|

Cedarwood oil as an alternative to xylene as a clearing agent in histopathological tissue processing – A comparative study

Abstract: Background: Clearing in histopathological tissue processing should be able to make the tissues translucent and clear for the tissues to be visible under light microscopy and should render the clearing agent to be miscible with the dehydrant and the impregnation wax in the preceding and following processing steps. Xylene is a gold standard clearing agent but increasing concerns about the potential carcinogenicity, implementing eco-friendly agents in routine histopathology is necessary. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It was not for the entire body of an animal with pigmentation. [12] showed that many specimens were preserved with resin for a long time without harm, knowing that this study did not refer to whole living bodies such as fish or other animals. Whereas [13] showed that many plants and insects were preserved as living organisms in the natural resin known as amber without human intervention making these living organisms an important subject for genetic studies due to their excellent preservation.…”
Section: Introductionmentioning
confidence: 99%
“…It was not for the entire body of an animal with pigmentation. [12] showed that many specimens were preserved with resin for a long time without harm, knowing that this study did not refer to whole living bodies such as fish or other animals. Whereas [13] showed that many plants and insects were preserved as living organisms in the natural resin known as amber without human intervention making these living organisms an important subject for genetic studies due to their excellent preservation.…”
Section: Introductionmentioning
confidence: 99%